Synthesis of 4-Halogenated 3-Fluoro-6-methoxyquinolines: Key Building Blocks for the Synthesis of Antibiotics - Flagstad, Thomas; Petersen, Mette T.; Hinnerfeldt, Daniel M.; Givskov, Michael; Nielsen, Thomas E. (Synthesis, 2014)
A practical and scalable 4-step route is presented for the synthesis of 4-bromo-3-fluoro-6-methoxyoquinoline and 3-fluoro-4-iodo-6-methoxyoquinoline from readily available 2,4-dichloro-3-fluoroquinoline with an overall yield of 81–85%. Halogenated quinoline building blocks have found much use in antimicrobial drug discovery, and the method reported here would be useful for the synthesis of these compounds.
Keywords: antibiotic; quinolone; fluorine; heterocycle; regioselectivity